Exploring Natural Phenomena with Pop-Up Books: A Tool for Early Science Literacy - Saripudin, Aip; Aulia, Runtah Eva; Mulyana, Asep; Magasida, Diani (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Early childhood science learning often remains dominated by verbal explanation and minimally interactive materials, limiting children’s engagement with natural phenomena. This study developed a rain-themed pop-up book designed to operationalise early science literacy as a staged progression from contact and curiosity to concept formation and concept acquisition. Using a Research and Development approach adapted from Borg and Gall in six stages, the product was refined through expert validation of content, media design and durability, and language, followed by practitioner appraisal and a limited classroom trial with 15 children aged 5 to 6 years in Cirebon City, Indonesia. After revision, feasibility ratings reached 95% for content, 95.83% for media design and durability, and 87.5% for language, while practitioner appraisal showed high practicality (average 95.83%). Children’s rubric-based observation scores increased from 49.53% before implementation to 83.79% after implementation across all indicators. These findings suggest that interactive, phenomenon-based print media can provide a grounded pathway for strengthening early science literacy in resource-constrained classrooms. The study contributes globally by offering a transferable design model linking familiar natural phenomena, staged literacy indicators, and tactile visual pedagogy in early childhood settings. Its practical implication is that teachers can integrate science inquiry into classroom activities through low-cost, contextually adaptable media. However, the evidence remains limited by the small sample, single-site trial, and absence of a comparison group and inter-rater reliability reporting. Future studies should test this model across diverse contexts, use comparative or longitudinal designs, and examine how similar media support science concepts and sustained literacy development.